"A cadastre for Mali?" The production of land titles and the challenge of property data on the periphery of Bamako. (February 2019) - Bertrand, Monique
Graphical abstract: Abstract: This article examines the massive and unregulated registration of land titles on the periphery of Bamako. These permanent titles were the focus of reform launched in 2014 for the establishment of a cadastre in Mali. The measures taken to improve land inventories excluded provisional and customary rights, however, and targeted urban and peri-urban environments more specifically. This article studies the terms for securing land tenure in a peri-urban environment in which the commodification of land has driven great competition but done little to encourage investment. The analysis underscores the challenges in exploiting the data that describe land titles. It highlights the numerous limitations, but also the informative potential in the context of ongoing urban sprawl. Finally, the article highlights how land speculation is tied to both the socio-economic characteristics of title holders and to enduring political weakness in the country.